Money Management in Multiple Sclerosis: The Role of Cognitive, Motor, and Affective Factors - Yael, Goverover; Nancy, Chiaravalloti; John, DeLuca (Frontiers in Neurology, 2019)
Introduction: Few studies have examined the motor, cognitive and emotional factors involved in effective money management in persons with multiple sclerosis (MS). The aim of this study was to assess money management in persons MS and examine whether cognitive, motor and emotional processes can predict money management. Methods: This study included 72 persons with MS and 26 healthy controls (HC). Using an a priori definition of efficient versus inefficient money management skills, based on the money management questionnaire (self and others), and performance on Actual RealityTM (AR) money management items, MS participants were divided into two groups: efficient or inefficient money management (MS Efficient- MM, n=34 vs MS Inefficient-MM, n=38). These groups were compared on cognitive, motor and emotional variables. Results: Participants in the MS efficient MM group performed significantly better on executive function and processing speed measures, as well as performance on the 25WT. The MS Efficient -MM group also showed significantly less affective symptomatology (depressive and state anxiety). Importantly, HC performed similarly to the Efficient MM group on these tests. Good executive functioning and low depressive symptomatology predicted efficient money management. Conclusions: This study characterizes some of the major problems and underlying impairments persons with MS are encountering in money management. Practitioners working with persons with MS should be aware that executive functions impairments together with depressive symptomatology could signal possible money management dysfunctions. The early identification of at-risk persons for money management difficulties could have a profound impact on the quality of life of this subsample of the MS population.